Local Audience’s Motivations who Watch TV Program that Use Local Language (Qualitative and Desciptive Research on the Audience of TV Program Kesah Budaya TVRI Central Kalimantan) - Pebrianti, Anisa (Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
The aim of this research is to find the motivations of audience who watched TV Program that use the local languageTVRI Kalteng as a local TV station in Central Kalimantan had an educative and entertaining program called Kesah Budaya or Keba. This program showed various informations about Central Kalimantan society and culture in Dayak Ngaju. Keba showed the uniqueness of Central Kalimantan that could be seen through the hosts, the language, the clothes, etc.Keba was the only talkshow presented by TVRI Kalteng that used local language during its show. The qualitative study with descriptive approach was guided by uses and gratifications theory to understand this research. Data were gathered using in-depth interview and observation. Those were analyzed by Miles and Huberman analysis technique.The study found thatthe local audience in PalangkaRaya had been motivated to watch the TV show Keba which was delivered in a local language due to the diversity of information about Central Kalimantan culture and the usage of the local language during the show. In addition, respondents watched the show since they concerned and interested in their local culture which is consideredas their true identity.